Sustaining Resilience: Tackling the Challenges of Maintaining a Robust Health Workforce and Improving Healthcare Delivery - , Ernest Chinedu OKOLI; , Saidu Malgwi HASSAN; , Kelechi Nelson ADINDU; , Nwoke Chukwuebuka Emmanuel; , Nelyn Akunna OKOYE (Archives of Current Research International, 2025)
The global healthcare workforce is facing an unprecedented crisis characterized by shortages, uneven distribution, and increasing burnout, particularly in low- and middle-income countries (LMICs). These challenges threaten healthcare delivery, deepen health disparities, and restrict access to essential services, especially in rural and underserved regions. With an estimated shortfall of 18 million healthcare workers by 2030, urgent action is needed to build a resilient and sustainable workforce. This review examines strategies to strengthen the healthcare workforce by highlighting evidence-based approaches that enhance retention, professional development, and mental well-being. Key areas of focus include workforce education and training, fair compensation, mental health support, and the integration of digital health technologies like telemedicine. Additionally, international collaboration and public-private partnerships (PPPs) play a crucial role in mobilizing resources and driving healthcare innovation. To provide a comprehensive analysis, this study employs a systematic review methodology, synthesizing peer-reviewed literature, policy reports, and case studies from various regions. The research primarily focuses on LMICs, where workforce shortages are most severe, while drawing comparisons from high-income countries to identify adaptable best practices. Thematic analysis categorizes findings into key intervention areas, including workforce training, retention strategies, digital health adoption, and governance reforms. By evaluating successful models and identifying gaps in current workforce strategies, this review offers practical, evidence-based recommendations to guide policymakers and healthcare leaders in building a more resilient and equitable healthcare workforce. Addressing these pressing issues is essential for ensuring that health systems can withstand future global health challenges.